Cost‐effectiveness of cervical length screening and progesterone treatment to prevent spontaneous preterm delivery in Sweden. (1st June 2022) - Wikström, T.; Kuusela, P.; Jacobsson, B.; Hagberg, H.; Lindgren, P.; Svensson, M.; Wennerholm, U.‐B.; Valentin, L.
ABSTRACT: Objective: To estimate the cost‐effectiveness of strategies to prevent spontaneous preterm delivery (PTD) in asymptomatic singleton pregnancies, using prevalence and healthcare cost data from the Swedish healthcare context. Methods: We designed a decision analytic model based on the Swedish CERVIX study to estimate the cost‐effectiveness of strategies to prevent spontaneous PTD in asymptomatic women with a singleton pregnancy. The model was constructed as a combined decision‐tree model and Markov model with a time horizon of 100 years. Four preventive strategies, namely 'Universal screening', 'High‐risk‐based screening' (i.e. screening of high‐risk women only), 'Low‐risk‐based screening' (i.e. treatment of high‐risk population and screening of remaining women) and 'Nullipara screening' (i.e. treatment of high‐risk population and screening of nulliparous women only), included second‐trimester cervical length (CL) screening by transvaginal ultrasound followed by vaginal progesterone treatment in the case of a short cervix. A fifth preventive strategy involved vaginal progesterone treatment of women with previous spontaneous PTD or late miscarriage but no CL screening ('No screening, treat high‐risk group'). For comparison, we used a sixth strategy implying no specific intervention to prevent spontaneous PTD, reflecting the current situation in Sweden ('No screening'). Probabilities for a short cervix (CL ≤ 25 mm; base‐case) and for spontaneous PTD at < 33 + 0 weeks and at 33 + 0 to 36 + 6 weeks were derived from the CERVIX study, and probabilities for stillbirth, neonatal mortality and long‐term morbidity (cerebral palsy) from Swedish health data registers. Costs were based on Swedish data, except costs for cerebral palsy, which were based on Danish data. We assumed that vaginal progesterone reduces spontaneous PTD before 33 weeks by 30% and spontaneous PTD at 33–36 weeks by 10% (based on the literature). All analyses were from a societal perspective. We expressed the effectiveness of each strategy as gained quality‐adjusted life years (QALYs) and presented cost‐effectiveness as average (ACER; average cost per gained QALY compared with 'No screening') and incremental (ICER; difference in costs divided by the difference in QALYs for each of two strategies being compared) cost‐effectiveness ratios. We performed deterministic and probabilistic sensitivity analysis. The results of the latter are shown as cost‐effectiveness acceptability curves. Willingness‐to‐pay was set at a maximum of 500 000 Swedish krona (56 000 US dollars (USD)), as suggested by the Swedish National Board of Health and Welfare. Results: All interventions had better health outcomes than did 'No screening', with fewer screening‐year deaths and more lifetime QALYs. The best strategy in terms of improved health outcomes was 'Low‐risk‐based screening', irrespective of whether screening was performed at 18 + 0 to 20 + 6 weeks (Cx1) or at 21 + 0 to 23 + 6 weeks (Cx2). 'Low‐risk‐based screening' at Cx1 was cost‐effective, while 'Low‐risk‐based screening' at Cx2 entailed high costs compared with other alternatives. The ACERs were 2200 USD for 'Low‐risk‐based screening' at Cx1 and 36 800 USD for 'Low‐risk‐based screening' at Cx2. Cost‐effectiveness was particularly sensitive to progesterone effectiveness and to productivity loss due to sick leave during pregnancy. The probability that 'Low‐risk‐based screening' at Cx1 is cost‐effective compared with 'No screening' was 71%. Conclusion: Interventions to prevent spontaneous PTD in asymptomatic women with a singleton pregnancy, including CL screening with progesterone treatment of cases with a short cervix, may be cost‐effective in Sweden. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.